1989
DOI: 10.1063/1.101237
|View full text |Cite
|
Sign up to set email alerts
|

Heavy carbon doping of metalorganic chemical vapor deposition grown GaAs using carbon tetrachloride

Abstract: Characterization of heavily carbondoped GaAs grown by metalorganic chemical vapor deposition and metalorganic molecular beam epitaxy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…A nonlinear power-law dependence of the electrical compensation on the DEALO mole fraction is again noted, as in the case of n-type GaAs. The results from a second similar sample grown with a higher carbon concentration at 9.73ϫ10 17 cm Ϫ3 are also shown in Fig. 9.…”
Section: Dealo-doped P-type Gaasmentioning
confidence: 65%
See 3 more Smart Citations
“…A nonlinear power-law dependence of the electrical compensation on the DEALO mole fraction is again noted, as in the case of n-type GaAs. The results from a second similar sample grown with a higher carbon concentration at 9.73ϫ10 17 cm Ϫ3 are also shown in Fig. 9.…”
Section: Dealo-doped P-type Gaasmentioning
confidence: 65%
“…3 for this Se-doped sample. The results from a second similar sample grown with a lower Se concentration at 5.14ϫ10 17 cm Ϫ3 are also shown in Fig. 3.…”
Section: ϫ3mentioning
confidence: 68%
See 2 more Smart Citations
“…The diffusion coefficient of C is, in general, at least one order of magnitude smaller than that of any group II acceptor in GaAs. Reference Abernathy, et al, 1989Saito, et al, 1988Kobayashi, et al, 1987Cunningham et a!., 1989Kuech, et a!., 1987Enquist, et a!., 1988Enquist, et al, 1988McLevige, et al, 1978lie gems, 1977Saito, et al, 1988 The local vibrational mode (L VM) of CAs was first reported by Newman. (Newman, et al, 1972) At 4K the CAs LVM appears at 583 cm-1.…”
Section: Basic Properties Of C In Gaasmentioning
confidence: 99%